2007
DOI: 10.1007/s10704-007-9104-3
|View full text |Cite
|
Sign up to set email alerts
|

Local strain energy to assess the static failure of U-notches in plates under mixed mode loading

Abstract: The averaged value of the strain energy density over a well-defined volume is used to predict the static strength of U-notched specimens under mixedmode conditions due to combined bending and shear loads. The volume is centered in relation to the maximum principal stress present on the notch edge, by rigidly rotating the crescent-shaped volume already used in the literature to analyse U-and V-shaped notches subject to mode I loading. The volume size depends on the ultimate tensile strength σ u and the fracture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
136
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 184 publications
(140 citation statements)
references
References 34 publications
4
136
0
Order By: Relevance
“…In previous works by the authors [28,[37][38][39] tensile tests with PMMA specimens at low temperatures had shown an almost linear elastic mechanical behaviour up to failure (see Fig. 8a).…”
Section: Resultsmentioning
confidence: 71%
See 4 more Smart Citations
“…In previous works by the authors [28,[37][38][39] tensile tests with PMMA specimens at low temperatures had shown an almost linear elastic mechanical behaviour up to failure (see Fig. 8a).…”
Section: Resultsmentioning
confidence: 71%
“…The problem becomes more involved if the loading symmetry is lost, i.e. when the notched structural component is subjected to mixed mode loading as widely discussed in previous works by other researchers [31][32][33][34][35][36] and also by the present authors [37][38][39][40][41][42].…”
Section: Introductionmentioning
confidence: 79%
See 3 more Smart Citations